MANGGALAMUDHA, KAJIAN GARAP SINDHEN - Junissa Salsabilla Nuhari Putri Atik Nurgiyatmi; Suyoto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This article entitled "Manggalamudha Gendhing Kethuk 2 Kerep Minggah 4, Laras Pélog Pathet Barang: A Study of Garap Sindhen" is to analyze and describe garap sindhènan gendhing Manggalamudha. The issues analyzed are garap céngkok, garap wangsalan and abon-abon, garap gregel and wiled, garap mlèsèt, garap angkat-sèlèh, garap mandheg, garap mungguh, and garap dynamics. These are reviewed using a number of concepts and theories in karawitan. The concepts applied are the concept of garap, the concept of mungguh, padhang-ulihan, and the concept ofmandheg. The concept of garap is used in creativity, the concept of mungguh is used for appropriateness in working on céngkok, the concept of padhang ulihan is used to determine wangsalan, while the concept of mandheg is used to work on mandheg in the inggah section of gendhing Manggalamudha which is worked on with andhegan cèngkok ayu kuning, andhegan kacaryan in the third kenong, and andhegan selingan. This research used qualitative research, data collection methods starting from the process of designing the work, determining the view (orientation), and determining the sources. Through literature study, observation, and interviews the author used as steps to collect data. The result of this research is garap mandheg in the inggah section of gendhing Manggalamudha which is worked with andhegan cèngkok ayu kuning, andhegan kacaryan in the third kenong, and andhegan selingan. The use of sindhèn garap in gendhing Manggalamudha is done with several garap, among others: wangsalan and abon- abon, garap gregel wiled, garap mungguh, lift technique, and garap dynamics. All sindhènan garap presented contain high aesthetic value in sindhènan gendhing Manggalamudha.